Impact of Regulations and Accreditation Standards on National Knowledge Examination Scores of Peruvian Medical Trainees: a Mixed-Methods Study - Pinto Salinas, Miguel Angel (2024)
Background: In the quest for excellence in medical education, regulations and accreditation standards emerge as beacons guiding the path to higher quality and competency at the national level. This study investigates their impact on changes in national knowledge examination performance among Peruvian medical trainees. Methods: A sequential explanatory mixed-methods approach was employed, beginning with a quantitative longitudinal analysis of data from the Peruvian Association for Medical Education database covering 45 medical schools from 2005 to 2023. Descriptive statistics were used to examine data trends; mixed-effects regression models were utilized to account for the nested structure of the data, allowing for a nuanced understanding of the standards’ impact over time and across different institutional contexts. To complement the quantitative findings, qualitative interviews were conducted with educational leaders to gain deeper insights into these standards’ implementation and perceived effects. This phase aimed to explore the nuances behind the quantitative results, capturing the experiences, challenges, and strategies employed by institutions in adapting to these standards. Results: In the quantitative analysis, a significant association was revealed between the implementation of these standards and improved examination scores, significantly influenced by factors such as association membership, institutional longevity, and geographical location. Qualitative interviews corroborated these findings, highlighting the standards’ role in enhancing educational quality and examination performance. However, challenges such as centralism and the need for a more integrated competency-based approach were identified. Conclusion: The study underscores the importance of national regulations and accreditation standards in increasing national knowledge examination performance and elevating medical education quality. These findings may advocate for more holistic approaches to competency-based medical education, incorporating educational standards, professional networks, and geographical considerations to optimize learning environments and healthcare outcomes.